Influence of microwave irradiation on hypochlorite decolorisation of synthetic dyes - Dušan Ž. Mijin; Dunja M. Dabić; Jelena M. Mirković; Bojan Đ. Božić; Branimir N. Grgur (Zaštita Materijala)
In this study three synthetic dyes were treated using hypochlorite or combination of hypochlorite and microwave irradiation in order to investigate factors which determine decolorisation of the investigated compounds. An azo dye (C.I. Reactive Orange 16 - RO16), an azo methine dye (C.I. Basic Yellow 28 - BY28) and an antraquinone dye (C.I. Acid Blue 111 - AB111) were used for experiments. Hypochlorite stability as well as the influence of microwaves on hypochlorite stability was also investigated.